1986
DOI: 10.3904/kjim.1986.1.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Antithyroid Autoantibodies in Normal Korean Population -Age, Sex Distribution and Its Relation to Thyroid Function-

Abstract: The prevalence of antithyroid autoantibodies and the relationship between the presence of autoantibodies and thyroid functions were studied in 848 apparently normal Korean adults with tanned red cell agglutination technique. Results are summarized as follows: 1) The prevalence of antimicrosimal antibody (MCHA) and antithyroglobulin antibody (TGHA) were 4.4% and 1.9% in 458 males, and 12.4% and 5.0% in 390 females, respectively. Both autoantibodies were more prevalent in female (p<0.001, p<0.01). 2) The age-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Another thyroid‐related autoantibody, Tg Ab, did not differ between NSV and SV. However, the Tg Ab positivity rate was higher in both groups than in the normal Korean population . The Tg Ab positivity rate was significantly higher in the late‐onset than in the early‐onset group.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Another thyroid‐related autoantibody, Tg Ab, did not differ between NSV and SV. However, the Tg Ab positivity rate was higher in both groups than in the normal Korean population . The Tg Ab positivity rate was significantly higher in the late‐onset than in the early‐onset group.…”
Section: Discussionmentioning
confidence: 69%
“…This was the only one of the three tested autoantibodies that differed significantly; however, this difference was only just significant ( P = 0.048). The rate of TPO Ab positivity was previously shown to be higher in both types of vitiligo than in the normal population . Additional analyses according to subject characteristics other than the type of vitiligo revealed significantly higher rates of TPO Ab positivity in patients with late‐onset vitiligo and in female patients.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In a large American survey which for anti-TPO and anti-TG respectively, and women aged 30 to 39 had a prevalence of 12.6% and 13.6% [35] . An earlier Korean study by Lee et al on 390 women, the prevalence of anti-TG was 5% [36] . In a more recent survey, Amouzegar et al measured anti-TPO antibodies in 3390 normal women, and 541 (16%) were found positive [37] .…”
Section: Discussionmentioning
confidence: 90%